Forgiveness Process for Students in Assignment Groups - Dian Juliarti Bantam (Da'wa Faculty of Islamic State University Salatiga, 2023)
This research was conducted to determine the dynamics ofstudent forgiveness in a work group. The number of subjects inthis research were 4 students who had been in a task group andhad felt disappointed and hurt by the treatment of members inone group. This research used a qualitative approach with aphenomenological research design. This was done to obtain morein-depth results regarding the dynamics of student forgiveness.The data analysis method used in this research was thematicanalysis. The results of this research showed the dynamics ofstudent forgiveness were different. From the four subjects, therewere subjects who had forgiven, there were also those who werein the process of forgiving and there were subjects who had notyet forgiven. The three aspects explained by Nashori (2011) werealso revealed in this research, meaning that four subjects broughtup aspects of forgiveness conveyed by Nashori (2011). Apart fromthat, the most important finding in the research was the existenceof forms of forgiveness from students and the process of givingforgiveness.